DETERMINAN CARBON EMISSION DISCLOSURE PADA PERUSAHAAN BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2017 - Sari Mujiani; Juardi Juardi; Feni Fauziah (JIAFE (Jurnal Ilmiah Akuntansi Fakultas Ekonomi), 2019)
Carbon emission disclosure is one of the corporate responsibility forms for environmental preservation that is presented in the financial statements. So that it raises carbon accounting, which is the companies to recognize, measure, record, present and disclose carbon emissions. This study aims to examine and obtain empirical evidence on determinants of carbon emissions disclosure at BUMN companies listed in Indonesia Stock Exchange. Several factors involved in this study, there are profitability, leverage, and firm size. In addition, population of this study is 20 BUMN companies listed in Indonesia Stock Exchange. Meanwhile, sample is selected using purposive sampling technique which produced 75 unit of analysis. This study also uses content analysis techniques on annual reports and/or sustainability reports in 5 years to measure carbon emission disclosure. Data collection is conducted by documentation technique. Moreover, panel data regression with Eviews version 9 applications to select panel estimation technique including chow test, hausman test and langrange multiplier test. Results indicate that profitability have significant and negative effect on carbon emission disclosure. While the leverage and firm size have significant and positive effect on carbon emission disclosure.